Temperature and Salinity Effects on Bioaccumulation, Gill Structure, and Radiation Dose Estimation in the Milkfish Chanos chanos Exposed to 137Cs - W.R. Prihatiningsih; H. Suseno; N.P. Zamani; D. Soedharma (PPIKSN-BATAN, 2016)
The present trend of global warming has led to an increase in seawater temperature and salinity. The effects of increasing salinity and temperature on the accumulation of 137Cs by milkfish Chanos chanos was studied under laboratory conditions to obtain information on Chanos chanos adaptability under environmental changes. The uptake of radioactive cesium by Chanos chanos increased with temperature of seawater. The concentration factors (CF) of 137Cs for temperatures of 25°C, 27°C, 29°C, and 31°C at steady state period were 5.25, 5.91, 6.78, and 9.98 mL g-1 for the whole-body of Chanos chanos. The concentration factors at steady state (CFss) of 137Cs for salinities of 26‰, 29‰, 32‰, and 35‰ were 6.23, 9.93, 9.24, and 6.86 mL g-1, respectively. After temperature exposure to 31°C, the fish gills showed hyperplasia of epithelial cells in branchial secondary lamellae, congestion of blood vessels, and hypertrophy of pillar cells. The fish from the treatment group exhibited hemorrhage between the branchial secondary lamellae and an abundance of mucous substance in comparison with control group. This study links radionuclide bioaccumulation data and monitoring data obtained in the field and laboratory experiment with radiation dose determined by ERICA Tools, an approach that will enable better linkages to be made between exposure and dose in Chanos chanos and its marine food web.Received: 2 November 2015; Revised: 1 July 2016; Accepted: 17 July 2016